The value of the expression as described in the task content is; 11.
<h3>What is the value of the expression?</h3>
The expression as described in the task content is; 3(4 - N) +8.
However, the value of N in this scenario is; 3.
Therefore, the value of.the expression is;
3(4 - 3) +8
= 3(1) + 8
= 3+8
= 11.
Read more on value of expressions;
brainly.com/question/625174
#SPJ1
Answer:
i don't now
Step-by-step explanation:
Answer: is B
Explanation: I’m guessing because that’s a black picture
<span>72÷p=8
</span>p = 72÷ 8
p = 9
hope it helps
Since f(x) is (strictly) increasing, we know that it is one-to-one and has an inverse f^(-1)(x). Then we can apply the inverse function theorem. Suppose f(a) = b and a = f^(-1)(b). By definition of inverse function, we have
f^(-1)(f(x)) = x
Differentiating with the chain rule gives
(f^(-1))'(f(x)) f'(x) = 1
so that
(f^(-1))'(f(x)) = 1/f'(x)
Let x = a; then
(f^(-1))'(f(a)) = 1/f'(a)
(f^(-1))'(b) = 1/f'(a)
In particular, we take a = 2 and b = 7; then
(f^(-1))'(7) = 1/f'(2) = 1/5